Albendazole on Soil Transmitted Nematodes among School Children in Kakamega County, Kenya - Teresia Ngonjo; Charles Mwandawiro; Ephantus Kabiru; Agola Eric Lelo (Albendazole on Soil Transmitted Nematodes among School Children in Kakamega County, Kenya, 2023)
Soil-Transmitted Nematodes (STNs) are roundworms transmitted through faecally contaminated soil. Globally, major STNs include Ascaris lumbricoides, Trichuris trichiura and hookworm (Necator americanus and Ancylostoma duodenale). School going children are mostly affected by STN infections. STNs cause malnutrition, intellectual retardation and cognitive deficits. They are distributed worldwide, Kenya included and they are of public health importance. Kenya has embarked on mass deworming programs since 2012.The study is entrenched in school mass deworming programs. Kakamega county has high edemicity of STNs and treatment using albendazole has been going on since 2009. The main objective of the study was to determine the effectiveness of a single 400 milligram dose of albendazole against STNs infections. A longitudinal study was conducted in selected public primary schools selected through random sampling from three randomly selected sub counties, Kakamega East, Kakamega Central and Kakamega South in Kakamega County, in Kenya. A structured checklist was used to establish demographics of the school pupils and schools’ WASH conditions. Kato Katz technique examined STN infections both at baseline and follow up survey. The prevalence of infection was determined as the percentage of children that tested positive for each STNs species to the total number of children examined. Intensity of infection was determined using Arithmetic mean of the number of eggs per gram of feaces. A total of 731 children in baseline from seven primary schools provided stools and were examined for STN infections. A post treatment survey was conducted after two weeks where total of 665 children were examined. Effectiveness of albendazole was analyzed using prevalence reduction and the fecal egg reduction rate (ERR). Data was analyzed using STATA version 12.0. Associations were assessed between WASH predictors and STNs; Infection prevalence of either gender or age group was analysed using Pearson chi-square test. Infection mean intensity was assessed using two sample independent t-test and significance for age group was assessed using ANOVA test. Prevalence of infections based on 95% CIs was calculated using binomial logistic regression. Arithmetic mean expressed mean egg counts and negative binomial regression model estimated mean intensity. At baseline, STNs prevalence was 44.0% (95% CI: 35.8 – 54.2). Common STN was Ascaris lumbricoides. 43.5%. The baseline STN mean intensity was 3674 eggs per gram. There was significant prevalence reduction of combined STN prevalence infection to 2.3% (PR=94.9%, P=0.001). STNs mean intensity was significantly reduced from 3674 epg to 59 epg (ERR=98.4%, P=0.001). Prevalence of T. trichiura significantly reduced, 0.8% to 0 (100%, P<0.001). Pupil latrine ratio was significantly associate with STN infection intensity (X2 = 0.875, df = 1, p=0.350) or intensity (X2 = 0.1944, df = 1, p=0.659). Hand-wash facility with water and soap did not associate with both lower infection prevalence (X2 =0.4667, p=0.495). In this study, mass treatment with Albendazole was highly effective on the STNs. These findings are important to Ministry of Health and Ministry of Education in assessing the national deworming guidelines and policies. Mass Deworming programmes be extended to communities to ensure all possible transmission focal points are covered.